Involvement of Sodium Nitroprusside (SNP) in the Mechanism That Delays Stem Bending of Different Gerbera Cultivars - Naing, Aung H.; Lee, Kyoungsun; Kim, Kyoung-Ook; Ai, Trinh N.; Kim, Chang K. (Frontiers in Plant Science, 2017)
We investigated the effect of sodium nitroprusside (SNP) on the delay of stem bending in gerbera cultivars Alliance, Rosalin, and Bintang, by examining several parameters, including relative fresh weight (RFW), bacterial density in the vase solution, transcriptional analysis of a lignin biosynthesis gene, antioxidant activities, and xylem blockage, which are all possibly associated with stem bending. All three gerbera cultivars responded to SNP by delaying stem bending, compared to the controls; however, the responses were dose- and cultivar-dependent. Among the treatments, SNP at 20 mg L-1 was the best to delay stem bending in Alliance, while dosages of 10 mg L-1 and 5 mg L-1 were the best for Rosalin and Bintang, respectively. However, stem bending in Alliance and Rosalin was faster than in Bintang, indicating a discrepancy influenced by genotype. According to our analysis of the role of SNP in the delay of stem bending, the results revealed that SNP treatment inhibited bacterial growth and xylem blockage, enhanced expression levels of a lignin biosynthesis gene, and maintained antioxidant activities. Therefore, it is suggested that the cause of stem bending is associated with the above-mentioned parameters and SNP is involved in the mechanism that delays stem bending in the different gerbera cultivars.